THE INFLUENCE OF WATCHING NEWS ABOUT CHURCH BOMBINGS IN SURABAYA ON THE PUBLIC PERCEPTION TOWARD THE VEILED MUSLIM WOMEN IN YOGYAKARTA - Adhiarso, Dendy Suseno (ULUL ALBAB Jurnal Studi Islam, 2019)
Wearing veil is the right for Muslim women in Indonesia. However, they should be careful with the recent social condition. Some people feel anxious, fear or even suspicious against veiled Muslim women. Moreover, after both electronic and social media provided information on terrorism cases, most people assume that it is done by Muslims. Based on the negative perception, the study aims to observe the effects of watching news about church bombing in Surabaya to people’s opinion about the veiled Muslim woman in Yogyakarta. The theory in this study is the cultivation and meaning of the message. This research is a quantitative method, precisely using a survey. The data are retrieved using questionnaires, and samples and are taken using purposive sampling technique. The result shows that R. Square is 0.227 which means that 22.7% variable factors’ perception on veiled Muslim women are affected after watching news about church bombing, while the 77.3% is affected by other variables. Based on the ANOVA, the value of F count equals to 28.827 with a 0.000 probability level (significance) which means watching a news about church bombing in Surabaya has significant impact on the public perception of the veiled Muslim women.